Hot melt extrusion assisted additive manufacturing of mixed polymeric 3D printed metoprolol succinate extended-release tablets for controlled oral drug delivery - Shubham Ghatole; Jannu Dilip; Makka Krupali Ashokbhai; Himanshu Vishwakarma; Subham Banerjee; Santanu Kaity (Chemical Physics Impact)
This study introduces an innovative methodology for fabricating extended-release metoprolol succinate (MS) tablets through the integration of Soluplus® and hydroxypropyl methylcellulose acetate succinate (HPMCAS) polymers, employing hot-melt extrusion (HME) and additive manufacturing technology. A carefully optimized polymer-plasticizer combination facilitated the production of extrudable filaments, which were subsequently used in three-dimensional printing (3DP) tablets via fused deposition modeling (FDM). The filaments were comprehensively characterized using tensile strength assessment, Fourier-transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). At the same time, micro-computed tomography (µCT) provided detailed analysis of the 3D-printed tablets. Filaments incorporating 10 % w/w citric acid as a plasticizer exhibited enhanced mechanical robustness, with tensile strength reaching 5.19 N, strain elongation of 29.2 %, and was found suitable for the fabrication of tablet dosage form with acceptable quality. Drug release , assessed in phosphate buffer at pH 6.8, revealed a controlled release profile, with 70 % of the active pharmaceutical ingredient (API) released over 6 h These results show the promise of using such techniques as platform technology for delivering similar categories of APIs. This developmental pathway can also be used for the fabrication of personalized medicines with adjustable drug release profiles.